The acquisition of generics - Kirkpatrick, JR (Wiley, 2024)
It has been argued that the primary acquisition of genericity in early child speech poses a problem for standard quantificational approaches to generics and instead motivates the claim that generics give voice to an innate, default mode of generalising. This paper argues that analogous puzzles involving the acquisition of A-quantifiers undermine the empirical support for a purely cognition-based approach to generics. Instead, these acquisition puzzles should be solved by generalising the core insight of the cognitive defaults theory to these expressions, reconciling formal semantic approaches with the role that cognitive development plays on lexical competence.